IMPACT OF MASS MEDIA ON PUBLIC CONSCIOUSNESS IN MODERN WORLD - Kundahbayeva Assel; Noda Larissa; Lozhnikova O.; Eskhuatova N.; Mukhamet kaliyeva Gulnar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The article examines the features of the activities of the media, the Internet and their influence on the formation of public opinion and public consciousness. Despite the fact that there is still no single view of the nature of such an impact, the relevance of studying the mass media is increasing, since they have unique capabilities to simultaneously transmit a large flow of information to millions of people around the world. It has been established that the methods of influencing the opinions and behavior of society are constantly being improved. It is concluded that at the present stage of development and functioning of the mass media, there are various problematic aspects that require more detailed consideration, one of which is the impact on the formation of public consciousness by manipulating the latter.